Analisis Penerapan Collaborative Learning dalam Pembelajaran pada Siswa Sekolah Dasar - Paulina Maria Ekasari Wahyuningrum (Departement of Mathematics Education, 2022)
This research analyzes the implementation of collaborative learning in elementary school students' learning. The literature review method was used as the primary approach. The analysis results indicate that collaborative learning has significant benefits, including improved critical thinking skills, social skills, teamwork abilities, and student motivation. However, challenges such as time management, task allocation, and teacher support need to be addressed. This study recommends providing training and guidance for educators, adequate resources and facilities, curriculum adjustments, and cooperation between teachers, students, and parents to support collaborative learning